2018
DOI: 10.1021/acsmedchemlett.8b00321
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation of Fluorescent 23-Hydroxybetulinic Acid Probes, and Their Cellular Localization Studies

Abstract: 23-Hydroxybetulinic acid (23-HBA) is a complex lupane triterpenoid, which has attracted increasing attention as an anticancer agent. However, its detailed mechanism of anticancer action remains elusive so far. To reveal its anticancer mode of action, a series of fluorescent 23-HBA derivatives conjugated with coumarin dyes were designed, synthesized, and evaluated for their antiproliferative activities. Subcellular localization and uptake profile studies of representative fluorescent 23-HBA probe 26c were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…To date, there have been few studies on 23‐hydroxybetulinic acid ( 14 ), although the majority of the existing works associate this triterpene to antitumor activity, with reported action against melanoma [51] and breast cancer cell lines [52] . Additionally, 23‐hydroxybetulinic acid presents cytotoxicity through mitochondrial pathway apoptosis, autophagy and cell cycle arrest in HL‐60, a human acute promyelocytic leukemia cell line [53] .…”
Section: Natural Pentacyclic Triterpenesmentioning
confidence: 99%
“…To date, there have been few studies on 23‐hydroxybetulinic acid ( 14 ), although the majority of the existing works associate this triterpene to antitumor activity, with reported action against melanoma [51] and breast cancer cell lines [52] . Additionally, 23‐hydroxybetulinic acid presents cytotoxicity through mitochondrial pathway apoptosis, autophagy and cell cycle arrest in HL‐60, a human acute promyelocytic leukemia cell line [53] .…”
Section: Natural Pentacyclic Triterpenesmentioning
confidence: 99%
“…Besides, HBA induced apoptosis of human leukemia HL-60 cells by inhibiting the expression of Bcl-2 and telomerase activity [8]. The results of subcellular localization and uptake profile studies of fluorescent HBA probe suggested that mitochondrion was the main site of probe accumulation in B16F10 cells [9]. The mitochondrion-targeted apoptosis in cancer cells along with the low toxicity in normal cells have made HBA derivatives as new promising chemotherapeutic candidates for the intervention of cancers.…”
Section: Introductionmentioning
confidence: 99%
“…HBA 4 was also used to perform esterification reactions [18,50,51]. Zhang et al prepared C-28 ester derivatives of HBA bearing different substituents 79 by the treatment of 3-oxo-HBA 78a with appropriate halides under basic conditions (Scheme 13) [18].…”
Section: Simple Transformationsmentioning
confidence: 99%
“…Another interesting report involving esterification reactions at 23-OH group of HBA 4 was published by Yao et al [51]. The authors synthesized a series of fluorescent HBA derivatives conjugated with coumarin dyes 82 and evaluated them for their antiproliferative activity.…”
Section: Simple Transformationsmentioning
confidence: 99%